0023 A prospective cohort study of the impact of return-to-work coordinators in getting injured workers back on the job. (21st August 2017) - Lane, Tyler; Lilley, Rebbecca; Hogg-Johnson, Sheilah; LaMontagne, Tony; Sim, Malcolm; Smith, Peter
Abstract : Background: Globally, 313 million missed at least four days of work in 2010 due to a work-related injury. Extended periods of work absence are costly and associated with poor health outcomes. Interventions that include return-to-work (RTW) Coordinators improve RTW outcomes, though they have often been investigated as part of a larger intervention package. We investigated whether Coordinator impact varies based on the stressfulness of interactions and whether it goes above and beyond functional aspects of their role and other workplace factors. Methods: A prospective cohort study of 632 workers in Victoria, Australia with more than ten days of compensation due to work-related injury. Participants rated the stressfulness of their Coordinator interactions, dichotomised into good and poor, and said whether they had a RTW plan. RTW plans are a functional responsibility of Coordinators. We analysed responses at baseline and six-month follow-up using logistic regression analyses, adjusting for demographic and workplace factors. Results: At baseline, RTW plans doubled odds of RTW and attenuated the impact of good Coordinator interactions, which had been associated with better RTW outcomes. At follow-up, the reverse was found: good interactions doubled odds of RTW while RTW plans were non-significant. Conclusions: The findings suggest that different aspects of Coordinator intervention have varied impacts on injured workers' RTW outcomes depending on their trajectory. Functional benefits improved outcomes among shorter-duration claims, while interpersonal intervention improved outcomes among longer-duration claims. There are implications for how Coordinators target and interact with injured workers and other ways of improving their effectiveness. Declaration of potential conflict of interest: : I (Tyler Lane) receive salary support from WorkSafe Victoria through a grant for another project, the Compensation and Return to Work Effectiveness (ComPARE) Project. All participants were WorkSafe clients, and WorkSafe conducted initial recruitment.